Reorientasi Pendidikan Islam Berbasis Maqāṣid al-Syarī‘ah sebagai Solusi atas Foundational Problem Zaman Modern: Penelitian - Asy’ari, Hasan; Lindayati, Eka; Makhrus, Imam; Noviani, Dwi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Islamic education in the modern era faces foundational problems, namely a crisis of value foundations, shifts in spiritual orientation, and epistemological fragmentation between religious sciences and general sciences. These issues create an imbalance in forming individuals who are faithful, knowledgeable, and virtuous. This article aims to conceptually analyze a new direction for the development of Islamic education through the maqāṣid al-syarī‘ah approach as a solution to these foundational crises. This study employs a qualitative method using a library research approach. The primary data sources are classical and contemporary literature on Islamic educational philosophy, theories of maqāṣid al-syarī‘ah, and issues of modernity in education. The findings indicate that maqāṣid al-syarī‘ah can serve as a paradigm for the reorientation of Islamic education because it integrates spiritual, intellectual, moral, and social dimensions. The application of values such as hifẓ al-dīn (preservation of religion), hifẓ al-‘aql (development of intellect), and hifẓ al-nafs (protection of life) becomes the foundation for establishing a holistic education system that is relevant to contemporary challenges. Thus, a maqāṣid al-syarī‘ah-based approach is not only capable of strengthening the philosophical foundations of Islamic education but also provides a new direction for shaping insān kāmil in the modern era.